2023
DOI: 10.1093/biolre/ioad059
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of uterus and placenta remodeling under high estradiol levels in gestational diabetes mellitus models

Abstract: The present study aimed to investigate the regulation of placentas and uterus remodeling and involvement of E2 in gestational diabetes mellitus (GDM). To achieve this, we established in vitro and in vivo models for GDM placentas by culturing BeWo cells under hyperglycemic concentration, and treating pregnant rats with streptozotocin (STZ). We evaluated the expression of angiogenesis-related proteins. The expression of the anti-angiogenic factor, excess placental soluble fms-like tyrosine kinase 1 (sFLT1) was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…In T1DM patients, estradiol levels are higher compared to the control group [ 37 ]. Moreover, based on the vivo experimental model, researchers from Korea found that the placenta and uterus were rebuilt in the rats with GDM, resulting in the upregulation of genes related to estradiol production [ 38 ]. This suggests that the estradiol may be a potential mediator between endometriosis and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In T1DM patients, estradiol levels are higher compared to the control group [ 37 ]. Moreover, based on the vivo experimental model, researchers from Korea found that the placenta and uterus were rebuilt in the rats with GDM, resulting in the upregulation of genes related to estradiol production [ 38 ]. This suggests that the estradiol may be a potential mediator between endometriosis and diabetes.…”
Section: Discussionmentioning
confidence: 99%